Experimental study on bumps formation textured by nanosecond laser on Ti6Al4V alloy. Issue 1 (27th February 2023) - Liu, Zhifang; Niu, Tong; Lei, Yaxi; Luo, Yuanxin
Abstract: The surface properties of biomaterials are the key factors for the success of artificial implants in the body. The creation of patterns on titanium alloys by laser surface texturing techniques can modify the surface to make it multifunctional. The evolution of the surface morphology of Ti6Al4V alloy textured by a nanosecond laser with 1064 nm wavelength in the air is studied. Laser surface texturing treatment is performed on the titanium alloy through different pulse numbers, power, pulse width and scan times to obtain different morphologies. The 2D cross‐section profile shows that the morphology can be divided into three types in the evolution process of various pulse numbers, powers and pulse widths: bump‐shaped, hump‐shaped and crater‐shaped. It is found that the effect of pulse width on morphology mainly depends on power. The effects of laser parameters on the height of bumps and the evolution of morphology are the main research points to analyse the topography evolution. The causes of bumps are also analysed. Energy dispersive spectrometer measures the area irradiated by the laser, and it is found that the oxygen content of the bump is up to 43.1%, which can speculate that the bump is the result of the oxidation reaction.